ANALISIS PENGUKURAN TINGKAT FATIGUE PADA PEKERJA TOWER CRANE (STUDI KASUS : PROYEK BDX DATA CENTER CGK3A - Kartika Hapsari; Kristin Febriyanti Zebua; Jonathan Saputra (Universitas Widyatama, 2025)
Fatigue is one of the main factors that can reduce performance and increase the risk of workplace accidents, especially for tower crane operators who are responsible for operating heavy equipment in construction environments. This study aims to compare the effectiveness of fatigue measurement using a mobile application versus a manual-based approach. It also aims to determine whether the features provided in the mobile application meet the needs of workers. The methods used include field observation, questionnaire distribution, interviews, and effectiveness testing through field studies involving tower crane operators at a construction project. The results of the study show that the use of mobile applications is more effective in measuring fatigue and more efficient in monitoring fatigue compared to manual measurements. It also enables early detection of potentially hazardous fatigue. Therefore, the mobile application can serve as an innovative solution to support occupational safety and risk management in the construction industry. However, additional features are needed in the application to measure fatigue factors such as travel condition and work environment condition.